Мир над пропастью: [роман] / Олег Рой - Рой Олег Юрьевич (Капризы судьбы, 2011)
Экземпляры: ф.18 (20160128) / Инвентарный номер: 477 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44